The Value of Caspase-3 after the Application of Annona muricata Leaf Extract in COLO-205 Colorectal Cancer Cell Line - Murdani Abdullah; Ari Fahrial Syam; Sofy Meilany; Bayu Laksono; Oryza Gryagus Prabu; Heri Setiyo Bekti; Lili Indrawati; Dadang Makmun (Gastroenterology Research and Practice)
Annona muricata, commonly known as soursop, contains annonacin, acetogenin, and polyphenol which are known to have chemopreventive effects on cancer. In this study, we tend to evaluate the apoptosis-inducing effect of soursop (Annona muricata) leaf extract on the colorectal cancer cell line COLO-205 through the activities of caspase-3 which is a marker of cell apoptosis. Cell cultures were incubated with soursop leaf with a concentration of 10 μg/ml and then compared with those of the incubated positive control leucovorin 10 μg/ml and placebo as a negative control. The apoptotic activity of caspase-3 was measured with ELISA. After the administration of each treatment in the colorectal cancer cell line COLO-205, the expression of caspase-3 activity was 1422 ng/ml after incubation with the extract of Annona muricata leaves, 1373 ng/ml after the administration of leucovorin, and 1297 ng/ml in the one with placebo. Annona muricata leaf extract elevated caspase-3 by 1.09 times compared to that of the pure cell line. Annona muricata leaf extract had a higher value of caspase-3 activity than leucovorin and placebo in the COLO-205 colorectal cancer cell line. These results may suggest that Annona muricata leaf extract had anticancer properties by enhancing caspase-3 activity which is a proapoptotic marker.